(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: The aim of this study was to explore differences in health care costs for asylum seekers from countries experiencing violent conflict and those from countries experiencing no violent conflict. METHDODS: Data were collected from a representative sample of refugees in an urban Swiss canton who were assigned to a Health Maintenance Organisation that covered all their health care costs. Cost differences for individuals coming from countries experiencing violent conflicts and from countries experiencing no violent conflict were tested by using multiple regression techniques and by controlling for confounding demographic, clinical and migration-related variables. RESULTS: Health care costs were higher for patients from countries with violent conflict. The higher costs could be attributed in part to increased frequencies of somatic diseases, however, the higher costs were linked primarily to the duration of the asylum seeker’s enrolment in the insurance programme, the number of visits to the medical facility, and the procedural status of the person’s application for asylum. CONCLUSIONS: Despite a higher prevalence of illness in patients from countries with violent conflict, the length of time spent in administrative “asylum seeker” status seemed to be the main driver of health care costs. Language barriers may be skewing results, with respect to the importance of specific diagnoses (especially mental health disorders), in driving costs upward. These results indicate a need for more comprehensive screening strategies for asylum seekers in receiving countries, particularly for those from countries in conflict.